Geometrical model for calculating the effect of surface morphology on total x‐ray output of medical x‐ray tubes. Issue 4 (17th February 2021) - Siller, Maximilian; Minkkinen, Mika; Bogust, Pamela; Jelinek, Alexander; Schatte, Jürgen; Bostrom, Neil; Greenland, Kasey; Knabl, Wolfram; Clemens, Helmut; Pippan, Reinhard; Maier‐Kiener, Verena
Abstract : Purpose: Correlation of characteristic surface appearance and surface roughness with measured air kerma (kinetic energy released in air) reduction of tungsten‐rhenium (WRe) stationary anode surfaces. Methods: A stationary anode test system was developed and used to alter nine initially ground sample surfaces through thermal cycling at high temperatures. A geometrical model based on high resolution surface data was implemented to correlate the measured reduction of the air kerma rate with the changing surface appearance of the samples. In addition to the nine thermally cycled samples, three samples received synthetic surface structuring to prove the applicability of the model to nonconventional surface alterations. Representative surface data and surface roughness values were acquired by laser scanning confocal microscopy. Results: After thermal cycling in the stationary anode test system, the samples showed surface features comparable to rotating anodes after long‐time operation. The established model enables the appearance of characteristic surface features like crack networks, pitting, and local melting to be linked to the local x‐ray output at 100 kV tube voltage, 10° anode take off angle and 2 mm of added Al filtration. The results from the conducted air kerma measurements were compared to the predicted total x‐ray output reduction from the geometrical model and show, on average, less than 10 % error within the 12 tested samples. In certain boundaries, the calculated surface roughness Ra showed a linear correlation with the measured air kerma reduction when samples were having comparable damaging characteristics and similar operation parameters. The orientation of the surface features had a strong impact on the measured air kerma rate which was shown by testing synthetically structured surfaces. Conclusions: The geometrical model used herein considers and describes the effect of individual surface features on the x‐ray output. In close boundaries arithmetic surface roughness Ra was found to be a useful characteristic value on estimating the effect of surface damage on total x‐ray output.